THE ACCEPTANCE AND UNDERSTANDING OF PRENUPTIAL MARRIAGE AGREEMENTS IN MALAYSIA - Ridzuan, Abdul Rauf; Asharudin, Eynnadiyah Nuraisyah; Mohammad Bakhtiar, Nurul ‘Atiqah; Ibrahim , Nur Hamizah; Ab Rahman, Zaizul; Luthfia, Amia; Anak Jeffry Douglas, Irvina Joan (I-iECONS e-proceedings, 2023)
Nowadays, people are looking to get married without considering what comes after. They are not aware of a prenuptialagreement that can be done to secure their rights and assets if divorce occurs. This study is done to find the awareness and acceptance level of prenuptial agreements in Malaysia. Prenuptial agreements have been the centre of a lot ofdiscussion and debate in Malaysia in recent years. Although some argue that such agreements violate the Malay tradition of joint property ownership, others consider them a relevant measure to protect against financial conflicts in the divorce scenario. Prenuptial agreements are chosen because of the increment of divorcees not getting their rights in alimony which is mandatory for the ex-husband to pay every month to help the ex-wife and their children for their monthly expenses. The minimum sample size was determined through Raosoft Calculator software. This survey included 324 respondents, and the sample was acquired using Google Forms. The findings of this study depicted that theprenuptial marriage agreement is accepted and understood by the public. (M=3.44).